Programming C# 10 : build cloud, web, and desktop applications - Griffiths, Ian, 1973- (O'Reilly Media, Inc., 2022)
Designed for experienced programmers, this book provides many code examples to help you work with the nuts and bolts of C#, such as generics, LINQ, and asynchronous programming features. You'll get up to speed on .NET 6 and the latest C# 9.0 and 10.0 additions, including records, enhanced pattern matching, and new features designed to remove "ceremony" to improve productivity.